The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1016/j.envpol.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and exposure to polycyclic aromatic hydrocarbons and their derivatives in a rural Chinese home through biomass fuelled cooking

Abstract: The concentration and composition of PAHs emitted from biomass cooking fuel were characterized in a rural non-smoking household in northern China. Twenty-two parent PAHs (pPAHs), 12 nitro-PAHs (nPAHs), and 4 oxy-PAHs (oPAHs) were measured in the kitchen, bedroom, and outdoors during both summer and winter. The most severe contamination occurred in the kitchen in the winter, where the daily mean concentrations of pPAHs, nPAHs, and oPAHs were 7500±4100, 38±29, and 8400±9200 ng/m3, respectively. Our results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
5
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(96 citation statements)
references
References 31 publications
4
75
5
2
Order By: Relevance
“…Dezhou, located at a transportation junction with busy motor vehicle and railway traffic, is also an industrial city and surrounded by several large coal fired power stations (Zhang, 2009). In comparison, local sources of PM 10 at rural village sites are dominated by coal and biomass fuel combustion in households (Ding et al, 2012;Shen et al, 2010b). For all rural field sites, there was no appreciable local pollution source and the measured PM 10 were either from nearby cities, towns, and villages or from remote areas through long-range transport.…”
Section: Spatial Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dezhou, located at a transportation junction with busy motor vehicle and railway traffic, is also an industrial city and surrounded by several large coal fired power stations (Zhang, 2009). In comparison, local sources of PM 10 at rural village sites are dominated by coal and biomass fuel combustion in households (Ding et al, 2012;Shen et al, 2010b). For all rural field sites, there was no appreciable local pollution source and the measured PM 10 were either from nearby cities, towns, and villages or from remote areas through long-range transport.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…It is well established that in northern China the air quality is worse inside of rural households than outside air and that the majority of residents spend more time indoors (Ding et al, 2012). Hence, the overall health risk facing rural residents should be much higher than for those living in cities.…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…9-NA was observed in the combustion of all types of wood . Furthermore, Ding et al (2012) reported one of the highest concentrations of 9-NA in NPAHs in particulate phase collected in rural Chinese homes that use biomass (firewood and corn residue) as fuel. Therefore, 9-NA is likely correlated with biomass burning, probably because of the low temperatures in biomass combustion and the high reactivity of PAH nitration.…”
Section: Ambient Concentrations Of Npahsmentioning
confidence: 99%
“…the environment (11) . Cooking foods at high temperature (grilling, roasting or frying) generates a large amount of PAH (5,12,13) .…”
mentioning
confidence: 99%